P PENGARUH LIKUIDITAS, PROFITABILITAS, STRUKTUR ASET, RISIKO BISNIS, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PERUSAHAAN - Nungki Pradita; Khoirul Annas, Khoirul Annas (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This paper was conducted in order to examine the effect of liquidity, profitability, asset structure, business risk, and sales growth through partial or simultaneous methods on capital structure. The population used in this paper is a manufacturing company, has been and is still listed on the Indonesia Stock Exchange in 2018-2020. The sample selection technique uses purposive sampling, namely through the determination of several conditions. Thus, obtained as many as 44 samples of companies. In this paper, the data analysis technique used is multiple linear regression analysis. Based on the test results, it is known that liquidity and asset structure partially have a significant negative effect. Meanwhile, profitability, business risk, and sales growth have no negative significant effect on the company's capital structure. Through simultaneous testing, liquidity, profitability, asset structure, business risk, and sales growth have an influence on the capital structure.